Effects of high temperature on the eggs of Aedes aegypti (L.) and subsequent stages developed therefrom - Khan, Humayun Reza; Rahman, Farjana (Dhaka University Journal of Biological Sciences, 2013)
The eggs laid by the emerged Aedes aegypti (L.) (Diptera: Culicidae) females were treated with high temperature at 35ºC at different exposure periods, viz., half an hour, one, two, four, eight and 24 hours, separately along with their control. At different exposure periods at 35ºC and control - the percentage of egg hatching ranged from 59 to 97; larval and pupal mortality ranged from zero to 12 and 3 to 14 per cent, respectively. Larval and pupal periods were 76 to 115 and 33 to 42 hours, respectively. Lengths of 2nd, 3rd, 4th instars were 3.615 to 4.518; 5.575 to 6.455 and 7.13 to 7.62 mm, respectively. Mean diameters of the head capsule of 1st, 2nd, 3rd and 4th instar larvae were 0.243 to 0.336, 0.387 to 0.476, 0.644 to 0.695 and 0.723 to 0.907 mm, respectively. Length of the cephalothorax of pupae was 1.49 to 1.907 mm. Body lengths of male and female adults were 2.9 to 3.00 and 3.33 to 3.51 mm, respectively. Dhaka Univ. J. Biol. Sci. 22(1): 9-20, 2013 (January)